Information System Architecture in Local Government (A Case Study at XYZ Local Government) - Thowimma, One; Muhammad Hanafi; Amrozi, Yusuf (TEKNOLOGI DITERAPKAN DAN JURNAL SAINS KOMPUTER, 2024)
Implementing information systems within public organizations often encounters failures, one of which stems from inadequate information system planning. This issue also occurs in local government sectors, where the procurement and development of information systems must be preceded by proper planning. Information system architecture—or the planning framework for developing an information system—is therefore essential. This study aims to describe an information system architecture model for local government as part of developing a strategic plan (blueprint) related to information technology (IT). The architecture is designed for the regional financial management sector, illustrating application architectures based on identified needs and providing guidance for IT implementation solutions within the local government.